2018
DOI: 10.1080/08037051.2018.1505425
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive hemodynamic monitoring as a guide to drug treatment of uncontrolled hypertensive patients: effects on home blood pressure in the BEAUTY study

Abstract: Drug selection algorithm based on non-invasive hemodynamic monitoring induced larger reduction in home BP compared to conventional drug selection in uncontrolled hypertensive patients referred to European Hypertension Excellence Centers. Although the main BEAUTY study was negative, these home BP measurements taken by patients themselves may suggest that the integrated hemodynamic monitoring is useful in patients with uncontrolled hypertension. This finding might depend on specific features of home BP measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Our neutral results are consistent with the findings of the BEAUTY Study, which showed that noninvasive hemodynamic assessment combined with a drug selection algorithm did not result in a better reduction of daytime SBP in ambulatory BP monitoring among uncontrolled hypertensive patients [16]. The subanalysis of home BP measurements in the BEAUTY study; however, showed that the drug selection based on hemodynamic monitoring significantly improved home BP after 6 months compared with the control group (P ¼ 0.002) [17]. Similarly, a randomized prospective controlled trial in 2016 using impedance cardiography (ICG)-guided antihypertensive therapy showed a greater BP reduction in the ICG-guided group among the patients with higher BP but did not significantly reduce BP among patients with slightly elevated BP [21].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our neutral results are consistent with the findings of the BEAUTY Study, which showed that noninvasive hemodynamic assessment combined with a drug selection algorithm did not result in a better reduction of daytime SBP in ambulatory BP monitoring among uncontrolled hypertensive patients [16]. The subanalysis of home BP measurements in the BEAUTY study; however, showed that the drug selection based on hemodynamic monitoring significantly improved home BP after 6 months compared with the control group (P ¼ 0.002) [17]. Similarly, a randomized prospective controlled trial in 2016 using impedance cardiography (ICG)-guided antihypertensive therapy showed a greater BP reduction in the ICG-guided group among the patients with higher BP but did not significantly reduce BP among patients with slightly elevated BP [21].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the systems report not only an estimation of the cardiac output and other hemodynamic modulators but also generates a hemodynamic profile expressed as hemodynamic map showing deviations of volemia, inotropy, chronotropy, and vasoactivity from their normal range (Supplementary digital Figure 1, http://links.lww.com/HJH/B545) [10]. The HOTMAN System has been validated against invasive measurement (thermodilution method) of the cardiac index (CI) [13] and has been used in previous studies, for example, to assess hemodynamic patterns in patients with various forms of hypertension, in obese patients [14], or to guide treatment decisions in patients with resistant or uncontrolled hypertension [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Some trials have demonstrated the usefulness of hemodynamic profiling combined with a treatment algorithm for hypertensive patients with other impedance cardiography devices [14]. However, our previous study on hemodynamic profiling with the HOTMAN system to guide the antihypertensive therapy in each individual patient provided similar office and ambulatory BP changes as achieved by clinical hypertension experts [13], although home BP was reduced more in the group with therapeutic decisions based on the HOTMAN measurements [27]. Based on the small additional value of HOTMAN measurements to guide therapy in difficult-to-control hypertension, we cannot recommend its application in general clinical practice yet, but we do believe the HOTMAN measurements are of pathophysiological interest in research, as used in the present study.…”
Section: Interpretation Of the Resultsthe Control Groupmentioning
confidence: 95%
“…Better monitoring is one way, use of decision support is another possibility, e.g. utilising non-invasive monitoring of hemodynamic parameters combined with a drug selection algorithm [32].…”
Section: Discussionmentioning
confidence: 99%